Respons Masyarakat terhadap Produk Pembiayaan BMT di Kartasura - Dimas Saputra (Academica: Journal of Multidisciplinary Studies, 2017)
This paper would like to see the public response to financing products of BMT. This research uses descriptive qualitative approach, data collected through interviews with citizens, as well as some public figures that have influence in society. To enrich the discussion, the author also made a literature review of books, news, and articles that are relevant to the problem of research. The results showed that people have not used the financing products of BMT. Financing products are less widely used by the community due to lack of promotion and socialization, and the existence of conventional banks which are still the main priority to get financing. Thus, it is still necessary efforts to socialize financing products of BMT, so its products are known and used by the community.Keywords:Baitul Maal Wat Tamwil (BMT), financing, response, community